Rethinking the 5 R's in Open Educational Resources: A Reuse Perspective - Scheunemann, Silvia; Brandão, Anarosa; Brauner, Daniela (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2018: Anais do XXIX Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2018.1729, 2018)
Open Educational Resources (OER) are digital learning resources available under public domain or open licenses that empower users with the 5Rs of freedom: reusing, reviewing, remixing, redistributing or retaining them for particular purposes. This paper states how reuse is related with the other Rs with the goal of paving the way to define traceability criteria for OER automatic quality evaluation.